A feasibility study on rail freight distribution with particular reference to Nestle Products (Malaysia) Sdn. Bhd. / Widiyati Shaik Ahmad Soekarno - Ahmad Soekarno, Widiyati Shaik (1995)
Continuous planning and constant improvements are the key factors that had assisted Nestle's success as the number one (1) player in the Malaysian food industry. In Nestle Products (Malaysia) Sdn. Bhd. (NPM), the efficiency of the distribution system is one of the elements that is of crucial importance to the company besides producing quality food products. This research attempts to find potential opportunities for the Supply Chain Department of NPM to use the rail freight service as a part of its distribution system. In this research, analysis are made on the reliability as well as the costs factors. It has been revealed that currently it is not feasible for Nestle to use the rail freight service as it is relatively costly and on the part of KTMB, lacks of reliability and capability in terms of the need for KTMB freight trains to share and give way to the passenger trains over a single track to Bangkok and Singapore. For example, the costs of rail freight distribution for SCM to Singapore is 47% more than the distribution costs by road, and the cost of distributing mixed products to Bangkok by rail is 37.4% higher than the distribution costs by sea. In addition, KTMB freight service frequently experience delay of more than 24 hours in its shipments to Bangkok. However, with the view that KTMB is on its way to modernise its system (which will enable them to provide reliable service) and Nestle is also going to face a substantial increase in its trade volume, it may be viable for Nestle to re-consider the idea of using the rail transport as part of its distribution system in the near future.